2012
DOI: 10.1515/hc-2012-0070
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antioxidant activity of a series of novel 3-chalcone-substituted 1,4-dihydropyridine derivatives

Abstract: New 3-chalcone-substituted 1,4-dihydropyridine (DHP) derivatives have been synthesized based on dimethyl or diethyl 2,6-dimethyl-4-phenyl-1,4-DHP-3,5-dicarboxylate. Their structures were confirmed by IR, 1H NMR, 13C NMR, and elemental analyses. The synthesized compounds were also screened for antioxidant properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Among them, thienyl substituted 1,4-DHPs have shown promising anti-oxidant activities ( Scheme 68 ). 98 Kruk et al (2020) reported the chemiluminescence properties of 4-flavonil-1,4-DHP derivatives 68 by spectrophotometry methods, which showed better light emission from the structure. From this study, all observed luminescence molecules showed superoxide dismutase activity due to the transformation of superoxide radicals ( Scheme 69 ).…”
Section: Synthetic Advancesmentioning
confidence: 99%
“…Among them, thienyl substituted 1,4-DHPs have shown promising anti-oxidant activities ( Scheme 68 ). 98 Kruk et al (2020) reported the chemiluminescence properties of 4-flavonil-1,4-DHP derivatives 68 by spectrophotometry methods, which showed better light emission from the structure. From this study, all observed luminescence molecules showed superoxide dismutase activity due to the transformation of superoxide radicals ( Scheme 69 ).…”
Section: Synthetic Advancesmentioning
confidence: 99%
“…Recently, Sun et al [ 68 ] reported about the synthesis and antioxidant activity of a series of novel 3-chalcone-substituted 1,4-dihydropyridine derivatives, based on dimethyl or diethyl 2,6-dimethyl-4-phenyl-1,4-DHP-3,5-dicarboxylate.…”
Section: 14-dihydropyridines: a Separate Group Of Bioantioxidantsmentioning
confidence: 99%
“…They have outstanding molar absorption coefficients and solvatochromic characteristics. Chalcones’ non-toxicity is another important property in comparison to other dyes; hence, chalcones are recognised as promising candidates for the continued progress of fluorescence/colorimetric probes in the chemical sensor sector 7 15 . The chalcones’ great sensitivity to metal ion concentrations allows them to examine micro-parameters of a biological entity that are connected to the polarity of the probe’s surroundings.…”
Section: Introductionmentioning
confidence: 99%